Problems of Staffing the Medical System in Surkhandarya Region and Reforms in the System (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
Surkhandarya region also had big problems in the field of medical services, which play an important role in the social life of the population. Medical centers, outpatient clinics, hospitals, polyclinics are in a very deplorable condition and have not been repaired for many decades. Supplying such medical institutions with qualified doctors was also unsatisfactory. Due to the old buildings of medical institutions, their equipment, medical supplies, and the extreme poverty of the material and technical base, most of the young people who graduated from medical schools quit their jobs and look for work in other places.